2009
DOI: 10.1002/adma.200900278
|View full text |Cite
|
Sign up to set email alerts
|

Magnetoelectric Effects in Complex Oxides with Competing Ground States

Abstract: The drive to develop materials with new multifunctional capabilities has rekindled interest in multiferroics-systems which are characterized by the simultaneous presence of, and coupling between, magnetic and electric order parameters. In naturally occurring multiferroics the magnetoelectric coupling is often weak, and new classes of artificially structured composite materials that combine dissimilar magnetic and ferroelectric systems are being developed to optimize order parameter coupling.[1-6] Here, we desc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
348
4

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 422 publications
(368 citation statements)
references
References 37 publications
16
348
4
Order By: Relevance
“…13 The energetic ordering of the e g orbitals on each Mn site as well as neighboring Mn sites profoundly affects the ground state magnetic properties. [14][15][16][17][18][19][20] Although structural distortions (e.g., Jahn-Teller or GdFeO 3 distortions) are common for bulk perovskite manganites, they only weakly remove orbital degeneracy. 13 With the development of epitaxial thin film growth techniques, it is possible to remove orbital degeneracy through straininduced Jahn-Teller-like distortions.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…13 The energetic ordering of the e g orbitals on each Mn site as well as neighboring Mn sites profoundly affects the ground state magnetic properties. [14][15][16][17][18][19][20] Although structural distortions (e.g., Jahn-Teller or GdFeO 3 distortions) are common for bulk perovskite manganites, they only weakly remove orbital degeneracy. 13 With the development of epitaxial thin film growth techniques, it is possible to remove orbital degeneracy through straininduced Jahn-Teller-like distortions.…”
mentioning
confidence: 99%
“…We realize this interface experimentally by using molecular beam epitaxy to deposit an integer number of unit cells of LSMO on a Nb-doped TiO 2 -terminated SrTiO 3 (001) substrate before depositing the ferroelectric BaTiO 3 thin film. 15 First principles calculations have shown that at a ferroelectric/LSMO interface, the termination of the ferroelectric polarization and presence of surface bound charge pull screening charges to the interface. [24][25][26] For out-of-plane ferroelectric polarizations, two interfacial states are possible: accumulation or depletion of holes, as illustrated in the left panels of 1.…”
mentioning
confidence: 99%
“…Note that the difference in magnetic moment persists at zero applied electric field, which excludes electrostrictive or piezoelectric effects (strain) as being the cause of the observed magnetoelectric effect. The magnetoelectric effect in the PZT/LSMO system is robust and has been observed in structures where the LSMO film has been grown by off axis magnetron sputtering Molegraaf et al (2009) The variation of the magnetization as a function of temperature for the two states of the PZT polarization is shown in Fig. 2(a) Molegraaf et al (2009);Vaz et al (2010c).…”
Section: Magnetoelectric Coupling In Pzt/lsmo Multiferroic Heterostrumentioning
confidence: 88%
“…Such fine control can be achieved with molecular beam epitaxy Vaz et al (2010d) or pulsed laser deposition Huijben et al (2008), where the film growth can be monitored layer-by-layer in real time by using the oscillations in the intensity of reflection high energy electron diffraction patterns. In the following, we provide an overview of the recent work demonstrating a large magnetoelectric coupling in PZT/LSMO heterostructures, as determined by probing directly the magnetic order parameter using local magnetooptic Kerr effect magnetometry Molegraaf et al (2009). By using advanced spectroscopy techniques, we show that the observed effect is electronic in origin, and that it results from a change in the valence state of the Mn cations with the change in the hole carrier density Vaz et al (2010b Fig.…”
Section: Magnetoelectric Coupling In Pzt/lsmo Multiferroic Heterostrumentioning
confidence: 92%
See 1 more Smart Citation